Water resources in Nepal: Institutional analysis based on legal provisions - Magar, Shyamu Thapa (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 4,069 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v9i0.1141 Occasional Papers in Sociology and Anthropology Vol.9 2005 p.194-227